Effects of Rederivation by Embryo Vitrification on Performance in a Rabbit Paternal Line - Daniel Juárez, Jorge; Marco-Jiménez, Francisco; Vicente, José Salvador (Frontiers in Animal Science, 2022)
Embryo cryopreservation is a valuable tool for maintaining genetic variability and preserving breeds and lines, allowing to assess the response to selection and enabling genetic diffusion. This study aimed to evaluate the impact of rederivation by embryo vitrification and transfer procedures on the growth and reproductive traits in a paternal rabbit line selected for average daily gain from weaning (28 days old) to fattening (63 days old). The rederived population were breed over two generations at the same time as a control population of this paternal line and, growth trait parameters (weights at weaning, end of the fattening period and average daily gain) and reproductive performance (kindling rate, litter size at birth and at weaning) were compared to three filial generations. Moreover, fetal growth and litter size components were assessed for the second generation by ultrasonography and laparoscopy. Differences in postnatal growth traits (end of fattening weight and average daily gain) were observed in the three generations assessed. However, fetal growth, litter size components and reproductive traits did not show significant differences. In conclusion, cryopreservation and embryo transfer processes cause changes in growth traits of reconstituted populations that influence the following generations, without changes in reproductive traits in a paternal line of rabbits.